Strengthening mechanisms of a near-α titanium alloy with high strength and impact resistance - Yongliang Qi; Yue Zhou; Xuefei Yu; Zhe Chu; Xiangdong Ding; Jun Sun (Journal of Materials Research and Technology)
Titanium alloys are widely used in aerospace and automotive applications. The strength and impact absorbed energy are two very important technical indicators, which represent the ability of resisting the damage of static load and impact force. In this work, we report a new discovery of obtaining a near-α titanium alloy with both high tensile yield strength (∼1050 MPa) and high Charpy impact absorbed energy (∼45 J). Microstructural and theoretical analysis reveal that the high strength is attributed to the dislocation strengthening and grain boundary strengthening, and the high Charpy impact absorbed energy of the alloy results from the combined effects of dislocation multiplication, twinning deformation and the transformation of α-Ti to FCC-Ti. These plastic deformation mechanisms can effectively absorb impact energy during impact deformation to ensure the alloy good impact resistance at high strength conditions. These strengthening mechanisms together provide us a new way to obtain near-α titanium alloys with superior resistance of both static-load and dynamic impact, for the requirement of more harsher application environments.